Balanced Scorecard Analysis of Amil Kompetensi Competence as a Model Rule for the Development of Zakat Institutions Resources (Study at LAZ Rumah Zakat Surabaya, East Java): (Analisis Balanced Scorecard terhadap Kompetensi Amil sebagai Rule Model Pengembangan Sumber Daya Lembaga Zakat (Studi di LAZ Rumah Zakat Surabaya, Jawa Timur)) - Basar Dikuraisyin (Islamic Economics Department, Faculty of Islamic Economics and Business, Sunan Ampel State Islamic University, Surabaya Indonesia, 2021)
Abstrack: This study seeks to analyze the competence of amil zakat institutions based on performance and accountability. This analysis is essential considering that amil is a determinant of the productivity and success of zakat management. Meanwhile, the reality of the performance of amil in Indonesia still presents a worrying performance. The principles of accountability and competence as regulated in the law are not yet detailed. The impact on the irregularity of the concept of zakat management institutions so far, therefore, this study answers how to analyze the Balanced Scorecard approach to the competence and accountability of amil in zakat institutions. This study was approached qualitatively analytically, and the primary source was obtained from the amil work system with Balanced Scorecard analysis as the embodiment of the evaluation approach. Data was obtained through documentation, interviews with standardized, systematic guidelines. After conducting the research, significant findings were found: first, the performance of amil at LAZ Rumah Zakat adheres to the principle of proportional balance. It is autonomous based on both the work aspect of amil and mustahik and muzakki. Second, the results of the balanced scorecard analysis on the competence of amil zakat in LAZ Rumah Zakat resulted in the following findings: 1) from a financial perspective, LAZ Rumah Zakat is said to be effective because there are indications of an increase every year both in the aspect of raising funds, the number of muzakki and reducing mustahik. 2) customer perspective (mustahik-muzakki), mustahik are satisfied with the protection and assistance from LAZ Rumah Zakat. 3) internal business perspective, namely the planning made by LAZ Rumah Zakat following the reality in the field. 4) the perspective of needs and learning, the amil performance of each division works optimally and helps each other. Keywords: Balanced Scorecard, amil competence, zakat institution Abstrak: Penelitian ini berupaya untuk menganalisis kompetensi amil lembaga zakat berdasar pada kinerja dan akuntabilitas. Analisis ini penting dilakukan mengingat amil merupakan penentu produktifitas dan keberhasilan pengelolaan zakat. Sementara realitas kinerja amil di Indonesia, masih menyuguhkan kinerja mengkhawatirkan. Prinsip akuntabilitas dan kompetensi yang diatur dalam undang-undang, masih belum rinci. Berdampak pada ketidak-teraturan konsep kelembagaan pengelola zakat selama ini. Oleh karena itu, penelitian ini menjawab bagaimana analisis pendekatan Balanced Scorecard terhadap kompetensi dan akuntabilitas amil di lembaga zakat. Penelitian ini didekati secara kualitatif analitis, sumber primer didapat dari system kerja amil dengan analisis Balanced Scorecard sebagai pengejewantahan pendekatan evaluasi. Data diperoleh melalui dokumentasi, interview dengan standart pedoman yang sistematis. Setelah dilakukan penelitian, ditemukan temuan penting, yaitu: pertama, kinerja amil di LAZ Rumah Zakat menganut prinsip keseimbangan proporsional (proportional balance) dan berbasis kewilayahan (autonomy based) baik pada aspek kerja amil maupun pada mustahik dan muzakki. Kedua, hasil analisis balance scorescard terhadap kompetensi amil zakat di LAZ Rumah Zakat menghasilkan temuan: 1) perspektif keuangan, LAZ Rumah Zakat dikatakan efektif karena ada indikasi peningkatan setiap tahunnya baik pada aspek penghimpunan dana, jumlah muzakki dan pengurangan mustahik. 2) perspektif pelanggan (mustahik-muzakki), mustahik puas dengan pengayoman dan bantuan dari LAZ Rumah Zakat. 3) perspektif bisnis internal, yakni perencanaan yang dibuat oleh LAZ Rumah Zakat sesuai dengan kenyataaan di lapangan. 4) perspektif kebutuhan dan pembelajaran, kinerja amil setiap devisi bekerja dengan maksimal dan saling membantu. Kata Kunci: Balanced Scorecard, kompetensi amil, lembaga zakat